Interpreting injury recidivism in a rural post-medieval male individual from Bucelas, Portugal - Antunes-Ferreira, Nathalie (2022)
This is the peer reviewed version of the following article: Interpreting injury recidivism in a rural post-medieval male individual from Bucelas, Portugal, which has been published in final form at https://doi.org/10.1002/oa.2943. This article may be used for non-commercial purposes in accordance with Wiley Terms and Conditions for Use of Self-Archived Versions